An Americium‐Containing Metal–Organic Framework: A Platform for Studying Transplutonium Elements. (30th September 2019) - Ridenour, J. August; Surbella, Robert G.; Gelis, Artem V.; Koury, Daniel; Poineau, Frederic; Czerwinski, Kenneth R.; Cahill, Christopher L.
Abstract: The synthesis, structure, and spectroscopic characterization of the first transplutonium metal–organic framework (MOF) is described. The preparation and structure of Am‐GWMOF‐6, [Am2 (C6 H8 O4 )3 (H2 O)2 ][(C10 H8 N2 )], is analogous to that of the isostructural trivalent lanthanide‐only containing material GWMOF‐6. The presented MOF architecture is used as a platform to probe Am 3+ coordination chemistry and guest‐enhanced luminescent emission, whereas the framework itself provides a means to monitor the effects of self‐irradiation upon crystallinity over time. Presented here is a discussion of these properties and the opportunities that MOFs provide in the structural and spectroscopic study of actinides. Abstract : Das erste Transplutonium‐MOF (Metall‐organisches Gerüst), [Am2 (C6 H8 O4 )3 (H2 O)2 ]⋅(C10 H8 N2 ), enthält dreiwertiges Americium und wird in Form von Am‐GWMOF‐6 erhalten. Es hat eine analoge Struktur wie das dreiwertige Lanthanoid‐MOF GWMOF‐6 und dient als Plattform zur Untersuchung der Am 3+ ‐Koordinationschemie und der gastmolekülverstärkten Lumineszenzemission.